The Alleged Tender Conspiracy in the Tanjung Pandan-Simpang Empat Road Widening Improvement Project, Bangka Province Based on Business Competition Law.: The form and suitability of tender rigging decisions based on Law No. 5/1999, regarding applicable business competition law and procurement of government goods and services. - Muhammad Ardin Ardiansyah; Sharda Arbianti (Reformasi Hukum Trisakti, 2024)
KPPU conducted an investigation into the Improvement and Widening of the Tanjung Pandan-Simpang Empat Road (Package 3) of Bangka Belitung Province for alleged violations of Article 22 of Law No. 5/1999 regarding Tender Conspiracy. The problem formulation is regarding what form of conspiracy is carried out by the parties reported parties I, II, III, and IV in KPPU decision Number 26/KPPUI/2019 and whether the panel's considerations in KPPU Decision Number 26/KPPU-I/2019 are in accordance with Article 22 of Law No. 5/1999. The research method use normative research methods and data sources according to secondary data. The results of the research and discussion found there are indications of horizontal collusion in the form of same IP address, format and typing errors in the RK3K document, the connection of the business actors, the deliberate omission of the Batching Plant document, the involvement of the tender committee in passing documents that indicate similarities. The conclusion obtained based on the research results shows that there is an element of "cooperation or coordination" to "create false competition", so that the Commission Council's decision say that the Reported Parties are not guilty is not in accordance with the provisions of Article 22 of Law no. 5/1999